The Gravity Model and Trade Efficiency: A Stochastic Frontier Analysis of Eastern European Countries' Potential Trade. (6th February 2014) - Ravishankar, Geetha; Stack, Marie M.
Abstract The opening up process of the eastern European countries is characterised by an increasing degree of trade integration with their Western neighbouring countries. Typically, the degree of East–West trade integration is assessed by comparing actual trade volumes with potential trade volumes projected from the gravity model parameters estimated for a group of countries that best represent normal trade relations. This approach, however, does not compare trade levels against a maximum level of trade feasible for the group of eastern European countries. This paper using a stochastic frontier specification of the gravity model is able to identify the efficiency of trade integration relative to maximum potential levels. The findings, based on a panel data set of bilateral exports from 17 Western European countries to the 10 new member states over the 1994–2007 period, indicate a high degree of East–West trade integration close to two‐thirds of frontier estimates, suggesting a low degree of trade resistances.